Lattice Modelling of Concrete-Ice Abrasion - Ramos, N. (author) (2015)
An increasing number of activities are moved into Arctic regions. As oil and gas companies are exploring the options in these regions, structures are required which can withstand the severe environmental conditions. Existing structures are subjected to heavy mechanical loads due to moving ice sheets. For concrete structures in particular ice abrasion damage has been observed on the surfaces. In extreme cases, ice abrasion has caused deterioration of the entire concrete cover on offshore structures. Most research on concrete-ice abrasion is quite empirical. Little is known about the material science of concrete-ice abrasion. As the theoretical frameworks supporting the concrete-ice abrasion process are quite limited, it is very difficult to predict service life deterioration of concrete structures and to define measures against ice abrasion damage. A numerical model in which the onset of wear in the concrete-ice abrasion process is simulated, is defined in order to increase the understanding of the mechanics of the abrasion process and to define measures against ice abrasion damage. Onset of wear is de?ned as the crack initiation and propagation in the concrete material due to ice loading. Hertz contact theory which predicts excessive tensile stresses on the concrete surface due to sliding of ice asperities is used as an analytical basis for the numerical model. In order to define an appropriate numerical model for the simulation of cracking in concrete, several modelling approaches can be employed. The simulations are performed on meso-scale, which means that concrete is modelled as a three-phase material in which paste, aggregates and the interface transition zone are distinguished. This is one of the main reasons to use a lattice model for the concrete. Contact between concrete and ice is decoupled. Decoupling of the two materials is justified as long as the materials exhibit linear elastic behaviour in the contact area. On meso-scale, ice crystals fail in a brittle compressive way under the loading conditions ...